Teaching life skills in the school library : career, finance, and civic engagement in a changing world - Woolls, Blanche; Hamner Williams, Connie (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2019)
This book shows librarians how to provide students with the practical information they need for a bright future. Chapters cover career readiness, financial literacy, and civic responsibility at each grade level.